Model of Risk Factors Identification: A Qualitative Approach to Mitigate Pilot Errors in Indonesia - Inne Yuliawati; Budi Sampurna; Tjhin Wiguna; Imam Subekti; Widura Imam Mustopo; Aria Kekalih (Indonesian Journal of Global Health Research, 2025)
Pilot errors accounts for 80% of accidents and 50% of serious incidents, thus identifying the risk factors is crucial to mitigation strategies. The research aimed to develop a model of pilot errors’ risk factors identification and mitigation by conducting a Focus Group Discussion (FGD) with stakeholders in Indonesia. This was a qualitative analysis by conducting hybrid FGD, divided into four groups of experts consisted of officials from the Directorate General Civil Aviation, human factors experts, active pilots and investigators from the National Transport Safety Committee, from 28 to 29 August 2024. The data was collected by transcribing verbatim transcript, then analysed using the Steps for Coding and Theorization and Content Validity Index. model was developed, consisted of pilots’ risk factors, divided into three themes, 16 sub-themes, grouped into internal and external factors, which can be identified by four activities and can be mitigated by three activities. The factors contributed to aviation safety are multifactorial and interrelated. The complexity of pilots’ risk factors involves a continuous assessment of identification and mitigation, emphasizes the adaptive collaboration among stakeholders. A significant contribution in aviation human factors data for the Safety Management System implementation in Indonesia.